GRAPHIC NOVELS AS A TOOL FOR BOOSTING READING COMPREHENSION IN EFL EDUCATION - Wisda Naura; Sholihatul Hamidah Daulay (Indonesian EFL Journal, 2024)
Students have challenges in acquiring proficiency in English reading due to several impediments that hinder their progress. Graphic novels have emerged as unconventional teaching materials in academic settings, providing a distinct viewpoint. However, the present research in this topic is limited. This research aimed to assess how the impact of graphic novels on improving students' reading comprehension. The study included sample of ninety senior high school students, and the researcher used a pre-experimental method to gather the data. Upon finishing the reading, students underwent reading comprehension evaluations. The findings revealed a clear correlation between reading graphic novels and improved comprehension. In this research, the researchers discovered that the findings obtained from the pre-test and post-test were very significant, since there was a noticeable rise in score values before and after the participants had therapy. The findings demonstrate that graphic novels have the capacity to impact and enhance students' reading comprehension abilities.